A14 WIDE VARIATION IN CLINICAL MANAGEMENT OF PAEDIATRIC EOSINOPHILIC ESOPHAGITIS: A CANADIAN EXPERIENCE. (4th March 2021) - Bortolin, K A; Ashok, D; Avinashi, V; Barkey, J; Burnett, D; Critch, J; Drouin, E; Griffin, J; Huynh, H; Marcon, P; Martinez, A; Persad, R; et al.
Abstract: Background: Eosinophilic esophagitis (EoE) is a chronic disorder treated by food elimination diet (FED), topical steroids and/or proton-pump inhibitors (PPI). Serial endoscopies and biopsies assess response to therapy. EoE management has evolved as guidelines are updated. Aims: To identify practice variation among Canadian paediatric gastroenterologists (PG) who care for children with EoE. Methods: An online survey using REDCap about decision-making in children with EoE was distributed to PG in Canada in November 2020. Results: 62 PG completed the survey (response rate 69%, 62/94). The majority work in academic centres (92%). 3 centers indicated an accrual of >50 new patients per year; 9/16 centres have >100 patients in follow-up. An EoE Clinic is present in 5 centres. Diagnosis: Familiarity with the 2018 AGREE and 2020 AGA EoE guidelines was found to be 57% and 67% respectively. Criteria required to diagnose EoE according to current guidelines were correctly indicated by 42% of PG. (Figure 1) . Endoscopy: The majority of PG (95%) adhere to guidelines in terms of required number and location of biopsies for the initial diagnosis. Ideal timing of repeat endoscopy after change in therapy in patients who are not in histological remission was 8–12 weeks by 67% of PG, timing in stable patients on maintenance therapy varied (33% only if patient is symptomatic). 25% used the EREFS Score in reporting endoscopic findings. Therapy: Improvement of symptoms was the highest ranked goal (64%), followed by remission of histologic findings (30%). A treatment algorithm was in place in 4 centers. The majority routinely assess adherence to therapy (73%) and consult a dietitian for FED (77%). Most (87%) do not consult an allergist for initial management. Preferred choices of 1 st -line therapy varied among PG (Figure 2). When FED was selected, 32% of PG started with 1 food, 32% started with 2 foods, most frequently excluding dairy, followed by wheat. 14 (26%) start with ≥6 FED. Prescription of budesonide slurry was consistent among PG with doses of 1 and 2 mg/day in children <10 and >10 years, respectively. Conclusions: The is the first Canadian study to assess the variation in management of children with EoE by PG. Overall, PG demonstrated good adherence to the guidelines in terms of initial diagnosis, but differences in maintenance therapy choice and timing of endoscopies. The results highlight a need for standardized management algorithms to deliver uniform care to this growing group. Grounding these guidelines in evidence will warrant a significant investment in further paediatric EoE research. Funding Agencies: None